TANGGUNG JAWAB KREDITOR ATAS HILANGNYA BARANG GADAI - Yustika Febriani, Amalia; Budi Arsika, I Made (Kertha Semaya : Journal Ilmu Hukum, 2014)
The title of this article is the responsibility of creditor for the loss of pawninggoods. It is a normative legal research that uses a statutory approach. The writeranalyzed that pawning agreement arises from the legal relation of mortgage agreementthat its repayment will be guaranteed by moving objects. In this regards, creditor shallbe liable to the pawn objects that lost or damaged, as stipulated in Article 157paragraph (1) of the Indonesian Civil Code, except for the case of force majeure.
Keywords: Liability, Creditor, Debtor, Pawn